The Impact of Trade Liberalisation on Economic Structure and Performance: Case of the OECS - Samuel, Thomas (Auckland University of Technology, 2007)
In keeping with global liberalisation trends and impelled by external liberalisation in terms of eroding preferential treatment in their principal export markets, the Organisation of Eastern Caribbean States (OECS)1 together with the wider Caribbean Common Market (CARICOM) region, has since 1993 embraced a policy of trade liberalisation as a strategy for growth and development. In large measure this was done through the phased implementation of a Common External Tariff (CET) involving a progressive lowering of tariff rates over the period, 1993-1998. The theoretical arguments in support of this policy change are based on the assumption of a positive link between trade liberalisation and economic growth. They contend that trade reforms that increase the outward-orientation/openness of trade regimes would result in structural change that reallocate resources in line with comparative advantage leading to exportled growth. This will then be followed by faster economic growth as countries benefit from efficiency gains, technology spillovers and other positive externalities.The thesis empirically assesses these claims against the nature of the impact of trade liberalisation on: (i) the export structure of the OECS and (ii) its economic growth performance. Using a comparative analysis in a dichotomous framework of ten-years before and after the policy reforms we find that in general the predictions of the underlying neo-classical trade model are not supported by the empirical evidence. There were indications of structural changes in exports in terms of reduced specialisation and competitiveness of traditional sectors and a steady shift of the macro-economy away from commodity production both agriculture and manufacturing towards services. Meanwhile the evidence suggests a revenue-neutral fiscal impact and no indication of systematic increase in technology transfer over the post-reform period.Using alternative estimation specifications in a single or simultaneous framework with and without fixed effects in a panel data setting, trade liberalisation was repeatedly found to be negatively associated with growth. In contrast openness was found to be positively correlated with both growth and export performance. At best a J-curve type impact of trade reforms on economic growth is deduced suggesting a long period of adjustment. However prospects for sustained growth seem remote on current indications suggesting the need for a reform of the international trade rules to cater to the special needs of LDCs and SIDS. In this pursuit a plausible alternative approach to the mode of implementation of trade liberalisation in is presented.